Air Pollution Management in Kosovo - World Bank (World Bank, Washington, DC, 2019)
Many cities in Kosovo suffer from poor air quality, with ambient concentrations of particulate matter with a diameter of 2.5 micrometers or less (PM2.5) significantly exceeding the national and European Union (EU) standards and global air quality guidelines for PM2.5 established by the World Health Organization (WHO). The air pollution in the capital city of Prishtina rivals that of big cities like Beijing, Mumbai, and New Delhi. Especially in winter, urban areas face severe smog episodes, caused by the increased demand for heat from the residential and commercial sector, which is mainly provided by burning solid fuels. Such levels of air pollution are unsafe for Kosovo's population of 1.9 million and cause significant deleterious health impacts. This report is one in a series of three reports on air quality management (AQM) in Kosovo, Bosnia and Herzegovina, and North Macedonia. It examines the nature and magnitude of ambient air pollution (AAP) in Kosovo. It provides estimates of the health burden and the economic cost associated with the health impacts of AAP, that is, PM2.5, in Kosovo. It also analyzes of the roles of various sources of PM2.5 emissions on ambient air quality in Kosovo at a national level. The institutional and policy framework for AQM in the country is examined, including contributions of other development institutions in supporting Kosovo in addressing air pollution. Furthermore, the report presents experiences of selected countries that have applied different policy, investment, and technical interventions for air pollution, prevention, reduction, and abatement. Finally, it provides recommendations for reducing air pollution in Kosovo.